Interoperability in Train Control Systems: Specification of Scenarios Using Open Nets - Padberg, Julia; Jansen, Lars; Heckel, Reiko; Ehrig, Hartmut (Proceedings of the conference on Integrated Design and Process Technology (IDPT 1998), Berlin (Germany))

Establishing PV-Education in Rio de Janeiro - Krauter, Stefan; Stephan, R. (International Journal of Electrical Engineering Education)

Hybrid Thermal Insulating PV Facade Elements - Salhi, M.; Triebel, C.; Lemoine, R.; Krauter, Stefan; Schroer, S.; Araújo:, R. G. (Proceedings of the 2nd World Conference on Photovoltaic Energy Conversion (Joint Congress of IEEE/PVSEC/EUPVSEC), Wien (Österreich), 3.–7. Juni 1998, Vol. 3, S. 2591–2594.)

Fortschritts–Berichte: Energetische Bilanzierung von Photovoltaik–Kraftwerken unter Berücksichtigung der Reduktion des anthropogenen CO2–Ausstoßes - Krauter, Stefan

Thermisch aktive PV-Module zur Fassadenintegration - Krauter, Stefan; Schroer, S.; Araújo, R. G.; Stephan, R. (Elftes Internationales Sonnenforum, 26.−30. Juli 1998, Köln (Deutschland), S. 368–375)

Aufbau einer universitären Ausbildungsmöglichkeit für photovoltische Energiesysteme in Rio de Janeiro - Krauter, Stefan; Araujo, R. G.; Stephan, R.; Hanitsch, Rolf; Onneken, K.; Schroer, S.; Quaschning, Volker (Elftes Internationales Sonnenforum, 26.−30. Juli 1998, Köln (Deutschland), S. 868–872)

Electronic Commerce Systeme als Anwendungsbeispiel für Evolutionstechniken - Engels, Gregor; Kolmschlag, Silvia

Unterstützung der Flexibilität eines Electronic Commerce Systems durch Evolutionstechniken - Kolmschlag, Silvia; Engels, Gregor (Proceedings of the workshop on "Integration heterogener Softwaresysteme" (satellite event of the GI-Jahrestagung Informatik 1998), Magdeburg (Germany))

Structured Transition Systems as Lax Coalgebras - Corradini, Andrea; Große-Rhode, Martin; Heckel, Reiko (Proceedings of the First Workshop on Coalgebraic Methods in Computer Science (CMCS 1998), Lisbon (Portugal))

Simple Modules for Grace - Heckel, Reiko; Hoffmann, Berthold; Knirsch, Peter; Kuske, Sabine (Selected papers of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT 1998), Paderborn (Germany))

Graph Transformation and Other Rule-Based Formalisms with Incomplete Information - Ehrig, Hartmut; Heckel, Reiko; Padberg, Julia; Rozenberg, Grzegorz (Proceedings of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT 1998), Paderborn (Germany))
A general framework is presented for extending graph transformation and other rule-based formalisms in such a way that transformations with incomplete information can be handled. This extension is motivated by the need to model the behaviour of open systems in different application areas using graph transformations and Petri nets. The following two problems are central within this general framework. 1. Characterization of transformations with incomplete information. 2. Recovery of information from incomplete transformations. A solution for these problems is presented for algebraic graph transformations and Petri nets using the new concepts of graph transitions based on double pullbacks and open nets based on autonomous actions for open places. Moreover, the problems are discussed for DNA-computing and other rule-based formalisms.

Double-Pullback Graph Transitions: A Rule-Based Framework with Incomplete Information - Ehrig, Hartmut; Heckel, Reiko; Llabrés, Mercé; Orejas, Fernando; Padberg, Julia; Rozenberg, Grzegorz (Selected papers from the 6th International Workshop on Theory and Application of Graph Transformations (TAGT 1998), Paderborn (Germany))

Classification and Comparison of Modularity Concepts for Graph Transformation Systems - Ehrig, Hartmut; Engels, Gregor; Heckel, Reiko; Taentzer, Gabriele (Pre-Proceedings of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT '98), Paderborn (Germany))
This paper presents a systematic approach for classifying and comparing modularity concepts that have been proposed for graph transformation systems. The approach is based on the following observation: Modules and module interconnections consist of basic specifications (forming, e.g., a module's body, import, or export interface), and relations between such specifications, like the implementation relation between export and body of a module. Hence, a natural approach for characterizing a module concept is to answer the following three questions: 1. What are the basic specifications? 2. Which relations between specifications are used? 3. How are specifications and relations combined to modules and interconnections? In this paper, these questions are considered in some detail for the following module concepts for graph transformation systems.

Model Checking Graph-Interpreted Temporal Formulas - Gadducci, Fabio; Heckel, Reiko; Koch, Manuel (Proceedings of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT 1998), Paderborn (Germany))

DPO Derivations via Disconnected Rules - Gadducci, Fabio; Heckel, Reiko; Llabrés, Mercé (Proceedings of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT 1998), Paderborn (Germany))

Event Processing in Mobile and Active Database Systems Using Broadcasts - Sauer, Stefan; Zukunft, Olaf (Proceedings of the 9th International Workshop on Database and Expert Systems Applications (DEXA 1998), Vienna (Austria))
The integration of active database technology into mobile database systems allows to limit the transfer of data between mobile computers and the stationary network. In order to employ such active database mechanisms, the rule processing component of traditional active database systems needs to be modified. This paper introduces a new model for event processing and presents a new algorithm for the composition of complex events in a mobile database environment. Furthermore, the model also takes into account the possibility of broadcast data. To validate the feasibility of the model, a prototype has been built using object-oriented technology.

Construction and Characterisation of Double-Pullback Graph Transitions - Ehrig, Hartmut; Heckel, Reiko; Llabrés, Mercé; Orejas, Fernando (Proceedings of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT 1998), Paderborn (Germany))

Job Rotation: Common Practice in Organisations? - Friedrich, A; Kabst, Rüdiger; Weber, W

Conference Proceedings: Sixth Conference on International Human Resource Management, Paderborn 1998. - Weber, W; Festing, M; Kabst, Rüdiger

Nonparametric Smoothing and Quantile Estimation in Time Series - Abberger, Klaus; Feng, Yuanhua; Heiler, Siegfried (Risk Measurement, Econometrics and Neural Networks. Contributions to Economics.)